(untitled) (Italian Journal of Public Health, 2012)
Since their first commercialization in 2007, the use of Direct To Consumer (DTC) genetic testing (GT) has rapidly increased. From the consumer viewpoint, the possibility to access genetic information without supervision of a medical doctor could allow for free choice and self-diagnosis (1), and in principle leads to an increased attention on...